Thermal and photostability of betacyanin from dragon fruit (Hylocereus polyrhizus) - Madzuki, Iffah Nadhira; Jin Samsudin, Nuradila; Nordin, Rumaisa; Mohamed Rasheed, Zahirrah Begam; Mohsin, Aliah Zannierah (Universiti Sultan Zainal Abidin, 2024)
Betacyanin derived from red beetroot is a permitted natural colourant, which has been widely used in food systems. However, a high dosage of betacyanin will give an undesirable odour and unfavourable earthy flavourdue to the presence ofgeosmin. An alternative source to replace betacyanin in beetroot is to extract betacyanin from red purple pitaya (Hylocereus polyrhizus). However, this natural pigmentis easily degraded under high temperature and sunlight.This research aims to determine the photostability and heat stability of the betacyanin using Response Surface Methdology at different pH, temperature, light exposure, and ascorbic acid concentrations. The parameters involved weretemperature, light, pH,and ascorbic acid at different ranges 65-95°C, 10-70 h, pH 3-7 and 0.1 g/mL-1.5 g/mL, respectively. The optimal betacyanin thermal stability was obtained at 77.428°C, pH 3 and 1.000 g/mL of ascorbic acid while the optimal photostability wasobtained at 44.726 h, pH 5.391 and 0.629 g/mL of ascorbic acid. Betacyanin also have high total phenolic content of 13.607 –18.071mg GAE/mL and antioxidant activitybased on DPPH scavenging activities of 546.549 μg/mL and 519.05 μg/mL. To conclude, this study proposed the optimum condition to retain the highest amount of betacyanin were temperature lower than 77.428°C, pH lower than pH 5.5 with 0.5 –1.000 g/mL of ascorbic acid. This information offers a useful guideline for food manufacturers to create the best storage condition for their products containing betacyanin.